Knowledge and practice of foot care among the patients of diabetic foot:a hospital based cross-sectional study - Sutariya, Pinakin K.; Kharadi, Ashish (International Surgery Journal, 2016)
Background: Good knowledge and practice regarding diabetic foot care will reduce the risk of diabetic foot complications and that will decrease the chances of amputation of the limb. Methods: Present study was hospital based cross- sectional study, conducted at a tertiary care centre of Ahmedabad city. Total 103 patients of diabetic foot, who had attended out patient department (OPD) of surgery from January 2015 to December 2015, were selected by purposive non probability sampling method. Twenty questions for knowledge of foot care and 14 questions for current foot care practice were included in the questionnaire and each positive answer was assigned one mark. Their knowledge and practice scores were classified as good, satisfactory and poor depending upon the score. For the knowledge and practice, if score was ≥70%, it was regarded as good, 50-69% was regarded as satisfactory and less than 50% score was regarded as poor. Results: Only 24(23%) patients had good knowledge, 51 (50%) patients had satisfactory knowledge and 28(27%) had poor knowledge about diabetic foot care. Majority of the patients, i.e., 53 (51%) had poor practice, 34 (33%) had satisfactory practice and 16 (15%) had good practice. Duration of the diabetes and frequency of diabetic foot had significant statistical association with knowledge and practices of foot care. Conclusions: Average Knowledge and poor practice were observed among the diabetic foot patients who have attended the OPD of surgery. It indicates need of giving proper knowledge to diabetes patients by education.